2006
DOI: 10.3892/ijmm.17.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induced proliferation and cytokine release in osteoblastic cells

Abstract: Abstract. Smoking has deleterious effects on osteoporosis and periodontitis both characterized by bone loss. Smoking also interferes with the protective effect that hormone replacement therapy (HRT) has on bone loss. Our study investigated two mechanisms by which smoking may affect bone metabolism: nicotine-induced proliferation and nicotine-induced cytokine secretion in osteoblasts. Two osteoblastic cell models were used: mouse osteoblasts derived from mouse calvaria and human osteoblasts. Thymidine incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
(28 reference statements)
2
33
0
3
Order By: Relevance
“…Another study demonstrated that nicotine increases Values are expressed as mean AE SD. secretion of the cytokines interleukin 6 (IL-6) and tumor necrosis factor a (TNF-a) (45) that could have their own effects on skeletal integrity. One could use this information to suggest a twophased effect of smoking on bone: an initial increase in remodeling activity followed by a long period of suppressed bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that nicotine increases Values are expressed as mean AE SD. secretion of the cytokines interleukin 6 (IL-6) and tumor necrosis factor a (TNF-a) (45) that could have their own effects on skeletal integrity. One could use this information to suggest a twophased effect of smoking on bone: an initial increase in remodeling activity followed by a long period of suppressed bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a human in vitro study, nicotine was found to upregulate the expression of IL-6 and tumor necrosis factor (TNF)-alpha. 23 Those factors can stimulate RANKL expression and are important for the induction and the further process of root resorption in the rat. 24,25 These findings suggest that the effect of nicotine on root resorption may act via various cytokines and signal pathways and further verify our hypothesis that the aggravated root resorption caused by nicotine is related to the elevated expression of RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nicotine apparently adds to preexisting periodontal inflammation [30,38]. Chemical evaluations have revealed that smoking results in accumulation of nicotine in periodontal fibroblasts [16] and at dental roots [10] and that nicotine promotes synthesis of inflammatory factors and osteoclastogenesis [17,19,52]. Also, nicotine promotes changes in the subgingival environment which has been suggested to facilitate the growth of periodontal pathogens [33].…”
Section: Effect Of Nicotine On Pdl and Bone Metabolismmentioning
confidence: 99%